Characterization of Mannose-Binding Lectin Gene Polymorphism Among Human T-Cell Lymphotropic Virus 1 and 2–Infected Asymptomatic Subjects - Pontes, G.S.; Tamegão-Lopes, B.; Machado, L.F.A.; Azevedo, V.N.; Ishak, M.O.G.; Ishak, R.; Lemos, J.A.R.; Vallinoto, A.C.R. (Human Immunology, 2005)
The present study investigated the association between mannose-binding lectin (MBL) gene polymorphism and the susceptibility to human T-cell lymphotropic virus (HTLV) infection in a group of 83 HTLV-infected asymptomatic subjects (62 HTLV-1 and 21 HTLV-2) and 99 healthy controls. Detection of MBL*A, MBL*B, and MBL*C was performed by amplifying a fragment of 349 bp (exon 1) and submitting the product to restriction fragment length polymorphism analysis with BanI and MboII endonucleases. Allele MBL*D was investigated by sequence-specific primer–polymerase chain reaction. The frequency of MBL*A, MBL*B, and MBL*D was 63%, 22%, and 15% among seropositive subjects and 70%, 14%, and 16% among healthy controls, respectively. Genotype differences were statistically significant (χ 2 = 11.57; p = 0.04); the presence of genotype BB was 9.6% among HTLV-infected patients compared with 1% among controls (χ 2 = 7.151; p = 0.019). A significant difference of the genotype frequencies between HTLV-1 and HTLV-2 infections was observed, but this result could be attributed to the number of investigated HTLV-1-infected subjects. The odds ratio to the presence of BB genotype was 10.453 (1.279 ≤ IC95% ≤ 85.40; p = 0.019). Results reveal a strong association between MBL polymorphism and HTLV infection. Presence of genotype BB may be associated with the susceptibility to HTLV, but further studies, with a larger number of individuals, will be necessary. MBL polymorphism could possibly have an impact on diseases associated with HTLV infection.